Frecuencia de acarosis y micosis cutáneas en pacientes atendidos en el Hospital Distrital Santa Isabel de El Porvenir -Trujillo, 2021 - Solorzano Morillas, Marianela Elisabeth (2023)
Dermatological diseases are an important public health concern, being mites and pathogenic fungi among the main causes of dermatosis. This study aimed to determine the frequency of acariasis and cutaneous mycosis in patients who attended Santa Isabel Regional Hospital of the district El Porvenir - Trujillo during 2021, and to determine in which age range and in which body area these pathologies occur with greater frequency. There was a total of 62 cases of patients with clinical suspicion of acariasis, or cutaneous mycosis that were treated at Santa Isabel District Hospital from January to December 2021. The data obtained were retrospective and prospective; retrospective data were obtained by reviewing laboratory records, whereas, for prospective data, skin scraping and observation with KOH test were performed. The results showed a frequency of acariasis, of 15%, in which 100% were children from 0 to 11 years old, and the most frequent lesion area was the thorax (78%). The frequency of cutaneous mycosis was 18%; the highest frequency, that is, 73%, occurred in children from 0 to 11 years old and, according to the lesion area, it occurred most frequently in the thorax area with 46%. It was concluded that acariasis, had a frequency of 15% and cutaneous mycosis of 18%, both pathologies occurred more frequently in children under 11 years old and the most frequent lesion area was the thorax.